A Web-like Personalized Advertising System for Interactive Digital TV - Cristo, Marco; Bitar, Ângelo; Guimarães, Bruno Ferreira; Penalber, Gabriel; Hanada, Raiza Tamae Sarkis; Teixeira, César; Melo, Erick (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2010)
As many other countries, Brazil is moving from an analogical to a digital TV system. Besides providing a better audio and video quality, an interactive digital TV (iDTV) system will make it possible to users interact with the TV in many ways. Such an interaction will contribute to the emergence of an array of new applications and possibilities, such as new approaches for interactive advertising. In particular, iDTV will provide an environment suitable for the placement of personalized advertisements which have the potential to be interesting for users and financing effective for advertisers and service providers. This kind of advertising approach has being successfully employed in another interactive environment, the Web, with large net gains for advertisers and content providers. Our aim in this work is to propose an architecture for a Web-like personalized advertising system (WPAS) and implement it for the Brazilian Digital Television System (ISDB-Tb), along with all the complementary mechanisms necessary in the ISDB-Tb. In particular, we present the design of the WPAS client module, describing the mechanisms necessary to the identification of the characteristics and interests of the users, the selection of the most appropriate ads, and their insertion into the content broadcasted by the service providers.